2011
DOI: 10.6060/mhc2011.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ferrocene-Modified Porphyrins by Reductive Amination Reaction

Abstract: Ferrocene-modified porphyrins were synthesized via the reductive amination reaction of ferrocenylpyrazolecarboxaldehydes and tetraphenylporphyrinamine. The steric hindrance of the ferrocene moiety was found to play the key role in this reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…FcPzNHH 2 TPP and Fc( i Pr)PzCH 2 NHTPP general procedure done according to modifications of previously reported [13b] . 5‐Ferrocenyl‐1‐phenyl‐1H‐pyrazole‐3‐carbaldehyde (0.5 mmol) with tetraphenylporphyrinamine (0.75 mmol) stirred (r.t.) for 20 min in 1,2‐dichloroethane.…”
Section: Methodsmentioning
confidence: 99%
“…FcPzNHH 2 TPP and Fc( i Pr)PzCH 2 NHTPP general procedure done according to modifications of previously reported [13b] . 5‐Ferrocenyl‐1‐phenyl‐1H‐pyrazole‐3‐carbaldehyde (0.5 mmol) with tetraphenylporphyrinamine (0.75 mmol) stirred (r.t.) for 20 min in 1,2‐dichloroethane.…”
Section: Methodsmentioning
confidence: 99%
“…Ferrocene has also been investigated as a substituent for porphyrins. Ferrocene is a weak electron donor, which has been used to generate long-lived charge-transfer states , and improve the catalytic activity in porphyrins . When ferrocene is directly appended to the meso position, replacing a phenyl ring in ZnTPP, the absorption spectra were slightly broadened and red-shifted due to the extended conjugation of the central porphyrin core. , The porphyrin-based emission was quenched by the addition of the ferrocene, and this quenching was shown to be able to be switched off by oxidizing the ferrocene. ,, When an alkyl linker is utilized between the ferrocene and porphyrin, the absorption is further broadened and red-shifted as the MOs are further delocalized .…”
Section: Introductionmentioning
confidence: 99%
“…Initially, we examined the regioselectivity of alkylation of ethyl 3-methyl-1H-pyrazole-5-carboxylate with 1-(ferrocenyl)alkan-1-ols in a two-phase aqueous-organic system using tetrafluoroboric acid as catalyst. It was found that the reaction involves the pyrazole nitrogen atom remote from the electron-withdrawing ester group [3]. The resulting esters were converted into the corresponding aldehydes in two steps [4].…”
mentioning
confidence: 99%
“…Preliminary testing of ferrocenyl porphyrin 3c and previously reported C-C-linked analog 4 [9,10] for cytotoxic effect against Staphylococcus aureus was carried out ( 12.52, 13.14 1.05 Table 1. Enantiomeric composition of racemic ferrocenylpyrazolyl porphyrins 3b-3d 2 × 10 -5 and 4 × 10 -5 M, which was enhanced under ultrasonic irradiation.…”
mentioning
confidence: 99%